2011
DOI: 10.1111/j.1365-2184.2011.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of transcription factor p53 and leptin in control of porcine ovarian granulosa cell functions

Abstract: The aim of our in vitro experiments was to examine the role of transcription factor p53 and the metabolic hormone leptin, in controlling basic functions (proliferation, apoptosis and secretory activity) of ovarian cells, as well as involvement of p53 in mediating or modulating actions of leptin, on ovarian cells. Porcine ovarian granulosa cells, transfected and non-transfected with a gene construct encoding p53, were cultured with leptin (at concentrations of 0, 1, 10 or 100 ng/ml). Accumulation of p53 and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Our results are the first demonstration of the ability of FSH to stimulate leptin release by granulosa cells. P4, T (Billig et al., ; Drummond, ; Sirotkin, ) and leptin (Sirotkin and Meszarosová, ; Sirotkin et al., ) are regulators of proliferation, apoptosis and hormone release from ovarian cells. Therefore, it is possible that P4, T and leptin at least partially mediated the stimulatory effects of FSH on ovarian cell proliferation, apoptosis and steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are the first demonstration of the ability of FSH to stimulate leptin release by granulosa cells. P4, T (Billig et al., ; Drummond, ; Sirotkin, ) and leptin (Sirotkin and Meszarosová, ; Sirotkin et al., ) are regulators of proliferation, apoptosis and hormone release from ovarian cells. Therefore, it is possible that P4, T and leptin at least partially mediated the stimulatory effects of FSH on ovarian cell proliferation, apoptosis and steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is a protein hormone that is produced by adipose and other tissues (Margetic et al., ), including ovaries (Siawrys and Smolinska, ; Sirotkin, ). Leptin increased proliferation and apoptosis (Sirotkin and Meszarosová, ; Sirotkin et al., ) and stimulated P4 release (Sirotkin and Meszarosová, ) from porcine ovarian granulosa cells. Therefore, leptin, such as FSH, may be a stimulator of ovarian functions.…”
Section: Introductionmentioning
confidence: 99%
“…A stimulatory effect of leptin on cell cycles proteins (PCNA, cyclin B1) and apoptotic peptides (bax) was also demonstrated in human ovarian granulosa cells [18], and leptin could induce expression of cyclin D1 and Mcl-1 (an anti-apoptotic factor) to promote cell growth by activating the PI3K/Akt pathway in human ovarian cancer [19]. In vitro experiments in porcine ovarian granulosa cells indicated that leptin stimulated accumulation of p53 (an inducer of apoptosis), bax and PCNA while it decreased expression of cyclin B1, and p53 mediated actions of leptin on ovarian cell apoptosis [20]. In chicken hens, leptin was shown to exert an anti-apoptotic effect in the ovary because in vivo injections of recombinant chicken leptin during fasting delayed cessation of egg laying and attenuated the fastinginduced apoptosis in the wall of F3-F1 follicles [21].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to vitamin D, leptin appears to act as a promoter of apoptosis [49]. For instance, in porcine ovarian granulosa cell, leptin treatment in vitro increased the accumulation of p53 and of apoptosis related (bax) and proliferationrelated (PCNA, cyclin B1) substances [49].…”
Section: Introductionmentioning
confidence: 99%